Evaluasi Dampak Kebijakan Program Nasional Pemberdayaan Masyarakat (Pnpm) Mandiri Perkotaan Terhadap Kondisi Ekonomi Masyarakat (Suatu Studi Di Kecamatan Sario Kota Manado) - Wongkar, Kevin Hizkia; Mandey, Jantje; Pombengi, Jericho Denga (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACK : The most prominent problems experienced by countries that are developing ispoverty. Starting in 2007, the Indonesian government launched a national program ofcommunity empowerment independent (PNPM). Manado city, especially in Sub Sario as thelocation of this research has been carried PNPM Urban, but according to the results ofpreliminary observations, indicated not optimal, where the community of beneficiaries have not /less feel the direct benefits of the program. Thus, this research, in addition to answering some ofthe problems also aims to: Analyze the impact / influence policy implementation of the NationalProgram for Community Empowerment autonomy Urban to improved economic conditions,particularly in Sub Sario Manado City, and knowing the differences in socio-economicconditions of the District Sario between conditions early (before the implementation of policiesPNPM) and the condition now (after the implementation of policies PNPM) Urban. This studyused a survey method explanation (explanatory survey method), the purpose of this study willexplain the impact of policy implementation of the National Program for CommunityEmpowerment (PNPM) independent Urban to economic conditions.The results showed that the average economic conditions after the application of PNPMUrban obtained 29.4 or in the ideal measurement scale of 0:59, or 59%, while the economicconditions prior to the implementation of PNPM Urban, an average of only 28.7 or of 0.574 or57.4%, so that there is a difference, which is about 1.6%. This means that an increase in theeconomic conditions of village communities in the District Sario Manado City after theimplementation of the PNPM Urban of 1.6%. It indicates that programs are implemented, bothurban and Infrastructure development programs empowering community programs, especiallycapacity building, strengthening business management and venture capital as well as the creationof the business climate can give a positive impact on the economic conditions of societyenhancement village itself.KEYWORDS : Impact Evaluation Policy, PNPM Urban